Pengembangan Media Cerpen Matematika Gembil Belajar Perkalian pada Siswa Kelas IV Sekolah Dasar - Hendrawan, Adinda Saskia Putri (Jurnal Pendidikan Matematika : Judika Education, 2026)
This research aims to examine the feasibility and practicality of the mathematics short story learning media titled "Gembil Belajar Perkalian" to facilitate the understanding of multiplication concepts among fourth-grade elementary school students. The method used is Research and Development (R&D) adapting the ADDIE development model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The results showed that the mathematics short story media "Gembil Belajar Perkalian" met the highly feasible criteria based on material expert validation of 82.50%, media expert validation of 89.58%, and practitioner validation of 91.67%, as well as meeting the highly practical criteria based on student response questionnaires with an achievement percentage of 93.60%. In conclusion, the mathematics short story media "Gembil Belajar Perkalian" is proven to be highly feasible and practical for use as an interactive learning tool in instilling the concept of multiplication as repeated addition for elementary school students.   Keywords: ADDIE, Feasibility, Mathematics Short Story, Multiplication, Practicality